2007
DOI: 10.1029/2007gl029632
|View full text |Cite
|
Sign up to set email alerts
|

On the MLT distribution of F region polar cap patches at night

Abstract: [1] Eight years of meridian scanning photometer data from Ny-Å lesund, Svalbard have been analyzed to study the occurrence of F region polar cap patches at night. In total 333 patches in 43 days were observed to hit the poleward boundary of nighttime auroras which is a unique signature of ongoing tail reconnection. The MLT distribution of patches is smooth and exhibit a bell shaped function symmetric around 23:25 MLT. The symmetry of the patch distribution about midnight indicates that patches populate the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 28 publications
(38 reference statements)
11
98
0
Order By: Relevance
“…Mitchell et al (2005) found phase and amplitude scintillations to be colocated with strong gradients in the Total Electron Content (TEC) at the edges of the high electron density streams. Furthermore, scintillation climatology studies by Spogli et al (2009) demonstrated enhanced scintillation levels around magnetic midnight, which were consistent with the Magnetic Local Time (MLT) distribution of polar cap patches at night (Moen et al 2007). By comparing the GPS data with radio instruments, Prikryl et al (2010) claimed that the polar cap patches are the main contributors to scintillation-causing irregularities in the polar cap.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…Mitchell et al (2005) found phase and amplitude scintillations to be colocated with strong gradients in the Total Electron Content (TEC) at the edges of the high electron density streams. Furthermore, scintillation climatology studies by Spogli et al (2009) demonstrated enhanced scintillation levels around magnetic midnight, which were consistent with the Magnetic Local Time (MLT) distribution of polar cap patches at night (Moen et al 2007). By comparing the GPS data with radio instruments, Prikryl et al (2010) claimed that the polar cap patches are the main contributors to scintillation-causing irregularities in the polar cap.…”
Section: Introductionmentioning
confidence: 55%
“…To conclude, the worst situation in the European Arctic sector can occur when polar cap patches are further structured by the substorm auroral arc dynamics, i.e., signal interferences with the auroral blob phenomenon around magnetic midnight. This can explain the scintillation climatology study by Spogli et al (2009) who attributed the scintillation peak around magnetic midnight to the statistical distribution of polar cap patches exiting the polar cap around magnetic midnight (Moen et al 2007). However, there is a need to carry out a statistical study to see if this is always true.…”
Section: Summary and Concluding Remarksmentioning
confidence: 97%
See 2 more Smart Citations
“…Two subsets of discrete polar aurora include polar cap arcs and polar cap patches. Polar cap arcs occur during quiet magnetic activity and northward IMF (Zhu et al 1997) and are 4 times more common in magnetic dawn than dusk (Hosokawa et al 2011), while polar cap patches exhibit a maximum at 23 hr MLT with intensities several times that of airglow (typically 1 kR; McEwen & Harrington 1991;Moen et al 2007).…”
Section: Review Of Airglow and Aurorae Variabilitymentioning
confidence: 99%